A possible home for a bizarre Carboniferous animal: is Typhloesus a pelagic gastropod?. (21st September 2022) - Conway Morris, Simon; Caron, Jean-Bernard
Abstract : By contrast to many previously enigmatic Palaeozoic fossils, the Carboniferous metazoan Typhloesus has defied phylogenetic placement. Here, we document new features, including possible phosphatized muscle tissues and a hitherto unrecognized feeding apparatus with two sets of ca 20 spinose teeth whose closest similarities appear to lie with the molluscan radula. The ribbon-like structure, located well behind the mouth area and deep into the anterior part of the body, is interpreted as being in an inverted proboscis configuration. Gut contents, mostly conodonts, in the midgut area demonstrate that Typhloesus was an active predator. This animal was capable of propelling itself in the water column using its flexible body and a prominent posterior fin. The affinity of Typhloesus as a pelagic mollusc remains problematic but may lie more closely with the gastropods. Heteropod gastropods share with Typhloesus an active predatory lifestyle and have a comparable general body organization, albeit they possess characteristic aragonitic shells and their origins in the Jurassic post-date Typhloesus . Typhloesus may represent an independent radiation of Mid-Palaeozoic pelagic gastropods.